Pemanfaatan Media dalam Penyebaran Pesan Wajib Pajak pada Masyarakat di Wilayah Kota Kendari - La Ode M. Nasir; Ashar Hasyim (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2023)
Communication media is seen as the right medium to influence the public in the process of delivering the taxpayer's message, so that the message conveyed can be well received by the public. The purpose of this study is to determine the use of the media in spreading the message of the taxpayer to the people in Kendari City. The results of the study show that the use of media in disseminating taxpayer messages uses 3 types of media, namely, Electronic Media consisting of television and radio, Print Media consisting of newspapers, billboards and banners, and Personal Media, outreach and exhibitions. From this study it resulted that in delivering promotional messages for taxpayers at KPP Pratama Kendari by using electronic media, namely television and radio and print media consisting of newspapers, billboards and banners, it was very effective in attracting the sympathy of taxpayers in Kendari City as well as the use of personal media, namely through exhibitions or expos and counseling is also very effective.